The contribution of MYC and PLK1 expression to proliferative capacity in diffuse large B-cell lymphoma. Issue 13 (10th November 2019) - Oon, Ming Liang; Hoppe, Michal M.; Fan, Shuangyi; Phyu, The; Phuong, Hoang M.; Tan, Soo-Yong; Hue, Susan Swee-Shan; Wang, Shi; Poon, Li M.; Chan, Hian L. E.; Lee, Joanne; Chee, Yen L.; et al.
Abstract: Polo-like kinase-1 (PLK1) regulates the MYC-dependent kinome in aggressive B-cell lymphoma. However, the role of PLK1 and MYC toward proliferation in diffuse large B-cell lymphoma (DLBCL) is unknown. We use multiplexed fluorescent immunohistochemistry (fIHC) to evaluate the co-localization of MYC, PLK1 and Ki67 to study their association with proliferation in DLBCL. The majority (98%, 95% CI 95–100%) of MYC/PLK1-double positive tumor cells expressed Ki67, underscoring the key role of the MYC/PLK1 circuit in proliferation. However, only 38% (95% CI 23–40%) and 51% (95% CI 46–51%) of Ki67-positive cells expressed MYC and PLK1, respectively. Notably, 40% (95% CI 26–43%) of Ki67-positive cells are MYC- and PLK-negative. A stronger correlation exists between PLK1 and Ki67 expression ( R = 0.74, p < .001) than with MYC and Ki67 expression ( R = 0.52, p < .001). Overall, the results indicate that PLK1 has a higher association than MYC in DLBCL proliferation and there are mechanisms besides MYC and PLK1 influencing DLBCL proliferation.